2007
DOI: 10.1080/17470210600955645
|View full text |Cite
|
Sign up to set email alerts
|

Distractor Repetitions Retrieve Previous Responses to Targets

Abstract: Response retrieval theories assume that stimuli and responses become integrated into "event files" (Hommel, 1998) in memory so that a second encounter with a specific stimulus automatically retrieves the response that was previously associated with this stimulus. In this article, we tested a specific prediction of a recent variant of stimulus retrieval theories as introduced by Rothermund, Wentura, and De Houwer (2005): In selection tasks where target stimuli are accompanied by distractors, responses to target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
289
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(325 citation statements)
references
References 23 publications
32
289
4
Order By: Relevance
“…Yet, more research is necessary to define further modulating factors of the effect. In addition it should be mentioned that the same pattern of distractor-response binding has been found with one-to-one stimulus-response mappings 9 . However, to exclude an influence of bindings between target and distractor stimuli, it is important to analyze response repetition trials that do not include target repetitions.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Yet, more research is necessary to define further modulating factors of the effect. In addition it should be mentioned that the same pattern of distractor-response binding has been found with one-to-one stimulus-response mappings 9 . However, to exclude an influence of bindings between target and distractor stimuli, it is important to analyze response repetition trials that do not include target repetitions.…”
Section: Discussionsupporting
confidence: 63%
“…Figure 3 is an example for data collected by Frings, Rothermund and Wentura (2007). Figure 4 summarizes the distractor-response binding effects of 33 experiments in different modalities 9,[18][19][20][21][22][23][24][27][28][29][30] . The effects become larger with more difficult tasks and thus with longer response times.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention and task relevance have also been manipulated at retrieval. Following the findings of Rothermund et al, it has been shown that distractor stimuli at encoding can modulate repetition priming at retrieval even when the stimulus remains a distractor (Frings, Moeller, & Rothermund, 2013;Frings, Rothermund, & Wentura, 2007). Such distractor-to-distractor effects suggest that, under certain experimental conditions, attention and task relevance are not necessary for both the encoding and the retrieval of S-R bindings (though see Moeller & Frings, 2014).…”
mentioning
confidence: 99%
“…Such distractor-to-distractor effects suggest that, under certain experimental conditions, attention and task relevance are not necessary for both the encoding and the retrieval of S-R bindings (though see Moeller & Frings, 2014). As in the literature for attended stimuli, these studies typically utilize a classification task at retrieval (e.g., the colour of a word), typically binary (e.g., Rothermund et al, 2005), though also four distinct response options have been used (e.g., Frings et al, 2007).…”
mentioning
confidence: 99%